Desirability of Compatibility in the Absence of Network Externalities - Economides, Nicholas (American Economic Review, 1989)
I compare the incentives firms have to produce individual components compatible with components of other manufacturers instead of "systems" composed of components that are incompatible with components of competing manufacturers. I show that, even in the absence of positive consumption externalities ("network" externalities), prices and profits will be higher in the regime of compatibility. Equilibrium total surplus could be higher in either regime. Both regimes overprovide variety compared to the surplus-maximizing solution.